The regulation of franchise in the Islamic finance industry: a case study of the Malaysian legal framework - Oseni, Umar Aimhanosi (2014)
With the increasing expansion of the global Islamic finance industry beyond its traditional strongholds, there is a gradual increase in the global franchising opportunities in Islamic finance. As one of the pioneering studies on franchise in Islamic finance, this paper examines the Malaysian legal framework on franchising within the Islamic finance industry. Over the years, there has been tremendous growth in the franchise industry in Malaysia and the Islamic financial institutions are not left out in this welcome development. While the franchise industry contributed RM24.6 billion or 2.8% to the Malaysian GDP in 2013, it has been projected that such contribution will reach RM25.4 billion by the end of 2014. The study adopts a qualitative legal method in analyzing the relevant legislations as they are applicable to Sharī‘ah-compliant business of Islamic financial institutions. The study finds that there is no specific framework for Sharī‘ah-complaint business in Malaysia, including Islamic finance business. Malaysia has vast opportunities in expanding its franchise industry through the amendment of the relevant legal framework to cater for Islamic finance business. This is expected to project Malaysia as a global hub for Islamic finance products and a destination for Sharī‘ah-complaint franchise businesses at the global level.